Glycerin bleaching process control structure / Zuriati Janin, Zakariah Yusuf and Mohd Nasir Taib - Janin, Zuriati; Yusuf, Zakariah; Taib, Mohd Nasir (UiTM Press, 2011)
This paper deals with the possibility of controlling the glycerin bleaching process that would improve the bleached glycerin quality using proportional-integral-derivative (PID) controller. An ideal and alternative PID control structures was analyzed. The controller parameters were adjusted and evaluated based on the available and wellknown tuning methods. The results show that the glycerin bleaching process control can be best achieve by using modified PID control structure with integral time absolute error (ITAE) (load) tuning method.